2021
DOI: 10.1108/ijchm-05-2021-0645
|View full text |Cite
|
Sign up to set email alerts
|

Frontline employee-driven change in hospitality firms: an analysis of receptionists’ personality on implemented suggestions

Abstract: Purpose Frontline employees’ suggestions are relevant for employee-driven organisational change because their knowledge is partially constructed from direct contact with customers and indirectly with competitors. The employee’s personality is a paramount individual characteristic that can exert a major potential influence on the proposal and implementation of those suggestions. This study aims to discuss the impact of the personality dimensions in the Big Five model (i.e. extraversion, neuroticism, conscientio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 100 publications
1
1
0
Order By: Relevance
“…In posing our research question, how do job, personal and contextual factors influence EIB, our findings reveal JC and each group of factors (personal and contextual) are important in nurturing EIB. In so doing, the research supports Do and Luu (2020) in highlighting the importance of employee’s individuality and behavior on organization’s performance and González-González et al (2021) suggestion that employee-driven organizational change is crucial for growth in the hospitality sector. The current study also advances the finding of Amabile et al (1996) who posit that workload pressure has a negative influence on creativity.…”
Section: Discussionsupporting
confidence: 54%
“…In posing our research question, how do job, personal and contextual factors influence EIB, our findings reveal JC and each group of factors (personal and contextual) are important in nurturing EIB. In so doing, the research supports Do and Luu (2020) in highlighting the importance of employee’s individuality and behavior on organization’s performance and González-González et al (2021) suggestion that employee-driven organizational change is crucial for growth in the hospitality sector. The current study also advances the finding of Amabile et al (1996) who posit that workload pressure has a negative influence on creativity.…”
Section: Discussionsupporting
confidence: 54%
“…According to social exchange theory, this study examines how individual employee creativity contributes to their novel ideas to enhance workplace organizational innovation behavior (Uzo & Ogbechie, 2017). The work studied creativity and motivation as internal aspects of frontline hospitality employees for making innovative organizational suggestions (González-González et al, 2021). Although the importance of fostering organizational creativity and open innovation is becoming more widely acknowledged, there still needs to be more empirical evidence on the impact of employee creativity and organizational innovation on enhancing SMEs' performance (Rumanti et al, 2023).…”
Section: Employee Creativity and Organizational Innovationmentioning
confidence: 99%
“…Goffman likened such workers to actors who literally 'take on' a character. The characteristics of the hospitality personality have been explored by many authors [8][9][10] and include, agreeableness, extroversion, openness to experience, conscientiousness, and emotional stability; although some research also reveals that neuroticism is also a hospitality characteristic in hotel receptionists. Alongside this research, other studies have identified the role of mood and personality in positive guest experiences, specifically service quality perception and customer satisfaction [11].…”
mentioning
confidence: 99%